Analysis of Community Economic Development Through the Agricultural Sector - Dorlan Habibi; Marliyah; Khairina Tambunan (LAA MAISYIR: Jurnal Ekonomi Islam, 2024)
This study examines the Analysis of Community Economic Growth through the Agricultural Sector in North Padang Lawas Regency. This study applies a descriptive qualitative research approach. This step is taken because the researcher will analyze various information in qualitative methods and then provide an interpretation of the data that has been collected. The information collected in the study is divided into two categories, namely: primary data and additional data. Primary data was obtained through direct observation in the field and interviews with sources from BPS (Central Statistics Agency) Padang Lawas Utara. Meanwhile, secondary data was obtained from journals and articles relevant to the research topic. The results of the study indicate that the community in North Padang Lawas has abundant natural resource potential, such as fertile soil and a climate that is conducive to agricultural activities. This provides significant opportunities for the development of various types of food crops and horticulture. In addition, the presence of the agricultural sector has a significant impact on the economic growth of the PALUTA community, considering that most of the population in the area works as farmers. Thus, in general the agricultural sector in North Padang Lawas has significant opportunities to develop, but requires special attention regarding sustainability, policy support, and increasing the ability of farmers in order to achieve maximum results.